(untitled) (Ameghiniana, 2013)
In the present paper a new genus, Protocosta, and 25 new species from the Huantrai-co arca, Neuquen Province, Argentina, are described. The new genus Protocosta is characterized by a carapace with subtrapezoidal outline in lateral view, anterior border rounded, posterior angular; subrectangular in lateral view with compressed extremities; left valve larger than right; suface ornamented by three ridges, dorsal, middle and ventral in position; the middle one may be absent or only poorly developed; marginal rim and denticles developed; surface reticulate. Eye tubercle clearly developed, subcentral node absent or only slightly insinuated. Inner calcified lamellae moderately wide, without vestibule; marginal zone with a modera te number (35) of marginal pore canals, simple, sometimes curved; muscle scar pattern, in a vertical row of four of the adductor and a frontal in V shape; hinge holamphidont. Sexual dimorpbism strong. Table 1 shows the vertical distribution, of the ostracode fauna, across the CP profil in the studied area; the sharp fauna! breacks between the levels CP-ll and CP-10, coincident with the Cretaceous-Tertlary boundary, and between the levels CP-25 and CP-22 which contain fresh water and marine faunas respectively are clear. A paleontological hiatus, which cornprises the Upper Maastricbtian, is registered by planktonic foraminifera. Table 2 shows the Loca! Range Zonation in the Huantrai-co area based on ostracode faunal assemblages.